What drives the decoupling progress of China’s civil aviation transportation growth from carbon emissions? A new decomposition analysis - Xiao Liu; Yancai Zhang (PLoS ONE, 2023)
Civil aviation carbon emission reduction is an inevitable requirement for achieving sustainable social development. Realizing the continuous expansion of air transportation scale while reducing the impact on the environment is particularly important. Therefore, it is necessary to accurately understand the relationship between civil aviation carbon emissions and the industry development. This study established a civil-aviation-pointed Tapio decoupling model to identify the decoupling state between transportation scale added and carbon dioxide emissions in China’s civil aviation sector. The index decomposition analysis method is further applied to decompose the factors influencing the changes in decoupling states. The empirical study generated three important findings. Firstly, the overall carbon emissions in the civil aviation sector are still growing, while the energy intensity has a tendency to fluctuate and decrease. Secondly, the relationship between carbon emissions and transport turnover is dominated by the expansive coupling, that is, the development of the civil aviation sector is still at the cost of the growth of energy consumption. Nevertheless, the overall decoupling stability is unstable, and the decoupling state is likely to be changed by many external factors. Thirdly, the energy intensity decoupling effect and industry structure decoupling effect are the main reasons for civil aviation carbon decoupling. Meanwhile, the improvement of national economic level during the research period is the dominant negative factor that restrains the carbon decoupling of the civil aviation sector.